1991
DOI: 10.1029/90jd02611
|View full text |Cite
|
Sign up to set email alerts
|

The iron catalyzed oxidation of sulfur(IV) in aqueous solution: Differing effects of organics at high and low pH

Abstract: We have studied the oxidation of sulfur dioxide by dissolved oxygen in highly dilute solutions with a new differential optical absorption technique. We measured the rate of oxidation catalyzed by iron(III) over a wide range of pH, ionic strength, and in the presence of various organic materials. The studies indicate that noncomplexing organic molecules are highly inhibiting at “high” pH values of 5 and above and are not inhibiting at “low” pH values of 3 and below. Furthermore, the order of the reaction with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
90
0
3

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(96 citation statements)
references
References 34 publications
(24 reference statements)
3
90
0
3
Order By: Relevance
“…Catalysis of S(IV) autoxidation by iron and manganese has been investigated in many laboratory studies (Conklin and Hoffmann (1988), Kraft and van Eldik (1989), Martin et al (1991), Grgić et al (1991), Berglund et al (1993), Kotronarou and Sigg (1993), Brandt et al (1994), Berglund and Elding (1995), Warneck and Ziajka (1995)). In Grgić et al (1998;, laboratory investigations showed that oxalate has a strong inhibiting effect on the conversion of S(IV) to S(VI) in the presence of Fe(II) or Fe(III) due to the formation of Fe(III)-oxalato-complexes.…”
Section: Introductionmentioning
confidence: 99%
“…Catalysis of S(IV) autoxidation by iron and manganese has been investigated in many laboratory studies (Conklin and Hoffmann (1988), Kraft and van Eldik (1989), Martin et al (1991), Grgić et al (1991), Berglund et al (1993), Kotronarou and Sigg (1993), Brandt et al (1994), Berglund and Elding (1995), Warneck and Ziajka (1995)). In Grgić et al (1998;, laboratory investigations showed that oxalate has a strong inhibiting effect on the conversion of S(IV) to S(VI) in the presence of Fe(II) or Fe(III) due to the formation of Fe(III)-oxalato-complexes.…”
Section: Introductionmentioning
confidence: 99%
“…A oxidação do S(IV) em fase aquosa, por O 2 , tem sido estudada por vários pesquisadores [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] , sendo que os resultados têm sido objeto de considerável controvérsia, em diversos aspectos. Para reações não catalisadas, a dependência com a concentração do oxigênio é discutida na literatura (Tabela 11).…”
Section: Reação De Oxidação Do S(iv) Em Presença De Oxigêniounclassified
“…Alguns autores estudaram a oxidação de S(IV) catalisada por metais em uma faixa de pH ampla e concluíram que o mecanismo da reação pode inclusive, ser alterado, a depender do pH. Assim, Martin e col. 13 sugeriram um mecanismo onde não há formação de radicais, para a oxidação de S(IV) catalisada por Fe(III), numa faixa de pH de 0 a 3, e um mecanismo por radical, para o mesmo processo, numa faixa de pH de 4 a 7. Segundo os autores, é impossível formular uma lei de velocidade geral, para um larga faixa de pH, sendo as seguintes equações propostas: , T=25 °C.…”
Section: -(99)unclassified
See 1 more Smart Citation
“…Iron also plays a central role in the biosphere, as an active centre of proteins responsible for O 2 and electron transfer by oxidase, reductase and dehydrase enzymes (Cotton and Wilkinson, 1988). Iron(II) is probably the preferred nutrient for phytoplankton (Martin et al, 1989) and iron(III) is considered to be an efficient catalyst for the autooxidation of SO 2 to SO 4 2 ; in clouds (Conklin and Haffmann, 1988;Martin et al, 1991). On the other hand, Fe(II) is important in the transport and storage of oxygen in higher animals by means of haemoglobin and myoglobin, while Fe(III) will not bind to oxygen (Nicholls, 1973).…”
Section: Introductionmentioning
confidence: 99%